Educational influences on ethnic identity development : a phenomenological study of minority young Muslim women in Guangzhou, China - Sha, Chunyan (Kulliyyah of Education, International Islamic University Malaysia, 2018)
Within the entire literature on identity studies of Chinese Muslim women, researches still remain limited. As ethnic identity is considered to be a fundamental aspect that provides an individual with a sense of belonging and commitment to a particular ethnic group, this exploratory phenomenological study using qualitative data analysis investigated the lived experiences of young minority Chinese Muslim women in order to gain an understanding of how they negotiate their ethnic identities within and outside their families. The study draws on data gathered from semi-structured interviews with nine young Muslim women who studied religious knowledge at various community-organized classes in the city of Guangzhou. Using integrated approach from developmental, social psychological, and acculturation theories as a conceptual framework, this study provides rich descriptions of the participants' identity negotiation, interpersonal interactions, and sense of belonging within a changing psychological, social and historical context. Based on participants' perceptions, the findings of this phenomenological study suggest (1) Ethnic identity is a dynamic process. (2) Social and cultural contexts have great effects on individual's ethnic identity development. (3) Ethnic identity is multidimensional: family, friends, gender, and religion play vital roles in the process of achieving positive ethnic identity. (4) Hijab issues are the major barriers for Muslim women living in the mainstream society. And single Muslim women faced difficulties looking for a partner in big cities like Guangzhou. (5) Ethnic identity is understood and internalized through community religious education. Based on the findings, it is recommended that practitioners, especially Muslim activists of current local communities to investigate prevention and intervention programs based on current educational and religious programs. Secondly, the results of this study suggest that educators and practitioners have the responsibility to help build a better connection of communication channel between policy makers and Muslim activists to hear and understand the needs of these minority Muslim women. It is also important to note that they may find out more possible ways of educating their members to consider religion as a potential source of empowerment and to discuss with the female members the ways in which they gain strength from their religious beliefs.